Tree species affect the vertical distribution of soil organic carbon and total nitrogen. Issue 6 (20th September 2022) - Steffens, Christina; Beer, Christian; Schelfhout, Stephanie; Vesterdal, Lars
Abstract: Background: Forest soils are considered sinks for atmospheric C. Many studies revealed that tree species and their mycorrhizal association affect forest floor and topsoil organic C (OC) and total N, while the knowledge of their effect on subsoil OC and N is still scarce. Aims: We aimed to identify (1) tree species and mycorrhizal association effects on forest floor, topsoil (0–30 cm) and subsoil (30–80 cm) OC and N stocks and vertical distribution and (2) drivers for soil OC and N distribution. Methods: We sampled forest floor, topsoil and subsoil under Fagus sylvatica L., Quercus robur L., Acer pseudoplatanus L. and Fraxinus excelsior L. in four Danish common garden experiments along a gradient in soil texture and determined OC and N stocks. Results: Total N (forest floor + soil) was higher under oak than beech, while total OC was unaffected by species. Forest floor C and N were higher under oak and beech, both ectomycorrhizal species (ECM), compared to under maple and ash, which are both arbuscular mycorrhizal species (AM). Relatively more OC and N were transferred to the topsoil under AM than ECM species, and this could be explained by greater endogeic earthworm biomass in AM species. In contrast, a higher proportion of OC was stored under ECM than AM species in the subsoil, and here OC correlated negatively with anecic earthworms. Subsoil N was highest under oak. Conclusions: Tree species and in particular their mycorrhizal association affected the vertical distribution of soil OC and N. Tree species differences in topsoil OC and N were not mirrored in the subsoil, and this highlights the need to address the subsoil in future studies on AM‐ versus ECM‐mediated soil OC and N stocks.